Open innovations in co-creation community platform : Bonding, crowding and complementor’ s engagement - YIU, Daphne W. (Institutional Knowledge at Singapore Management University, 2024)
This study underscores how community bonding and crowding mechanisms are intertwined to facilitate complementor’s engagement in a co-creation community platform. Co-creation community serves as both a social place for a firm and a valuable source of open innovation via the active involvement of its members. Using social identification and linguistic theories, we posit that affective bonding mechanisms, aroused and conveyed by linguistic cues in online computer-mediated communication, play an important role for complementor’s community identity and hedonism, thus stimulating their continued engagement in contributing creative ideas in the co-creation community platform. In addition, strategic coopetition theories also highlight the incentives given by community crowding mechanisms. As such, we further posit that the bonding and crowding mechanisms are intertwined to influence complementor’s continued engagement. Using a crawled set of 20,278 ideas and 780,840 comments from an exemplary brand co-creation community platform during 2008 and 2020, we find supporting evidence to our hypotheses. Our study sheds new light on the community interaction aspects of open innovations in an ideation platform by highlighting the underlying bonding and crowding mechanisms in a co-creation community.